Organic syntheses : (John wiley & sons, 2003)
The revised title, Organic Syntheses Based on Name Reactions, reflects the notion whereby many new reagents and reactions are now being referred to by their names. The inclusion of over 155 new stereoselective and regioselective reagents or reactions including asymmetric syntheses, brings the total to over 540. Features that will be invaluable to the reader include over 3000 references, a names index, reagent index, reaction index and a functional group transformation index. The latter of these indexes will allow the reader to search for conversions of one functional group